Compliance with the faecal calprotectin test in patients with inflammatory bowel disease - Maréchal, Chloé (United European Gastroenterol J, 2017)
BACKGROUND: We investigated, for the first time, levels of compliance with faecal calprotectin test in inflammatory bowel disease patients. METHODS: All consecutive adult inflammatory bowel disease patients having been prescribed an faecal calprotectin test between December 2014–July 2015 were included. At their next visit to the hospital, patients had to return a stool sample for the faecal calprotectin test and answer a simple questionnaire: ‘Have you brought a stool sample? If not, why not? If so, did you encounter any difficulties when collecting the sample? Were you aware of faecal calprotectin before being asked to take the test?'. RESULTS: One hundred and one patients were included (50 men; 77 patients with Crohn’s disease). The range age was 40 years (19–68). Eighty-nine patients were being treated with infliximab, 10 were on vedolizumab, and two were not being treated with a biologic. Thirty-seven patients (35%) had performed the faecal calprotectin test. Eighty-one patients (80%) had not been aware of faecal calprotectin before being asked to take the test. Of the 64 patients who did not take the test, the prime reasons for non-compliance were forgetfulness (n = 49, 76.6%), a lack of perceived benefit for the test (n = 7, 11%), constipation (n = 5, 7.8%), refusal to handle faeces (n = 2, 3.1%), and difficulty collecting the stool sample (n = 1, 1.5%). CONCLUSION: Only one-third of the patients performed the faecal calprotectin test. The main reason for non-compliance was forgetfulness. Our present results emphasise the need for better patient education on the importance of complying with faecal calprotectin testing and the future of faecal calprotectin testing at home.